Tool wear of poly crystalline diamond in cutting Ti-6Al-4V alloy with high-pressure coolant supplied - Wada, Tadahiro; Okayama, Kazuki (2017 8th International Conference on Mechanical and Aerospace Engineering (ICMAE), 2017)
Titanium alloys have high strength, low density and corrosion resistance, and are used for aircraft engines and airframe manufacture. For dimensional accuracy, titanium alloy is machined using a metal removal process. High-speed cutting is an effective method for improving productivity. As the cutting temperature increases significantly in high-speed cutting, the tool materials require both good wear-resistance and heat-resistance, and the cutting parts must be cooled to achieve efficacy and efficiency. In this study, Ti-6Al-4V was turned with a high-pressure coolant supplied, and the chip configurations and tool wear were experimentally investigated. The following results were obtained: (1) In turning with high-pressure coolant supplied, the effectiveness of chip breaking performance was improved. In this case, the chip length was shorter with the increase in the coolant pressure. (2) In the case of a cutting speed of 7.50 m/s, large wear on the cutting part was observed at cutting with conventional-pressure coolant supplied by both the CVD coated tool and the cermet tool. (3) In the case of cutting with the conventional-pressure coolant supplied by the cBN tool, tool wear of the PCD tool was smaller than that of both the CVD coated tool and the cermet tool. (4) In comparing cutting with the conventional-pressure coolant supplied and cutting with the high-pressure coolant supplied using the cBN tool, the tool wear in cutting with the high-pressure coolant supplied was slightly smaller than that in cutting with the high-pressure coolant supplied. (5) Comparing the cBN tool and the PCD tool in the case of cutting with the high-pressure coolant supplied, the PCD tool could cut to a cutting distance of 4521 m. (6) In the case of cutting with the high-pressure coolant supplied by the PCD tool, which has a large diamond particle size, Ti-6Al-4V could be cut at the higher cutting speed of 12.50 m/s. (7) In the case of cutting with the high-pressure coolant supplied by the PCD tool, the tool wear of the PCD tool decreased with the increase in the diamond particle size.